Patient selection for VV ECMO: have we found the crystal ball? - Ahuja, Abhilasha; Shekar, Kiran (Journal of Thoracic Disease, 2018)
Extracorporeal membrane oxygenation (ECMO) has emerged as a promising intervention for supporting patients with severe cardiorespiratory failure refractory to conventional management (1,2). As the technology is becoming safer, familiar and easier to use, the application of ECMO is likely to increase. However, ECMO still is invasive with significant potential for complications, resource intense and may present economic challenges to the health system (3). Risk prediction models were developed to help the clinicians identify the patients who would benefit from ECMO. However, these models should not be cumbersome, be easy to calculate and have good calibration and discriminatory power.